Analisis Pengaruh Budaya Organisasi dan Motivasi Kerja terhadap Kinerja Pengelola melalui Kepuasan Kerja (Studi pada Pengelola Program Pemberdayaan Masyarakat di Kota Jayapura Provinsi Papua) - Youwe, Ronny France; Sudiro, Achmad (Universitas Brawijaya, Indonesia, 2014)
The objectives of this research determine and analyze: the influence of organizational culture and work motivation toward job satisfaction; the influence of organizational culture, work motivation and job satisfaction toward toward administrator performance; the effect of job satisfaction as the mediator organizational culture and work motivation toward the administrator performance program community empowerment in Jayapura City Papua Province. Respondents of this study chairperson, secretary, treasurer and assistant tanaga community development programs in the city of Jayapura as many as 156 people. The instrument to collect the data was used a questionnaire, while the measurement scales used in this study are Likert scale. The analysis tool is used path analysis. The results of the study showed that organizational culture significantly influence job satisfaction and administrator performance. While no significantly effect of work motivation to job satisfaction but a significantly effect on the administrator performance. Job satisfaction is a partial mediating effect of organizational culture on the administrator performance, this suggests that organizational culture can result in administrator performance without going through job satisfaction. Job satisfaction is not a mediating influence between work motivation on the administrator performance.